Tanggung Jawab Hukum Rumah Sakit dalam Kasus Pelayanan Pasien Jiwa: Tinjauan Teori dan Praktis Hukum - Bianda Adeti Patriajaya; Muhammad Rifani; Lusiana Pratiwi Sukmajaya; Ahmad Ma’mun Fikri (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Mental health services in hospitals pose complex legal and ethical challenges, particularly in safeguarding the rights and safety of patients with psychiatric disorders. Incidents involving self-harm or harm to others during hospitalization raise critical questions about institutional accountability. This study adopts a normative and juridical approach to examine the legal responsibilities of hospitals—civil, administrative, and criminal—under Indonesian legal frameworks, notably Law No. 18 of 2014 on Mental Health and Ministry of Health Regulation No. 54 of 2017. Through the analysis of legal doctrines and selected case studies, the findings reveal structural weaknesses in the implementation of psychiatric care, including limited human resources, inadequate medical documentation, and insufficient adherence to standard operating procedures. These issues significantly hinder the effectiveness of legal protection for psychiatric patients. This paper underscores the urgent need for regulatory harmonization, improved oversight mechanisms, and capacity building among healthcare providers to ensure the delivery of humane, accountable, and legally compliant mental health services.